PENGARUH SEXTING TERHADAP KELEKATAN ROMANTIS PADA DEWASA AWAL DI KOTA BANDUNG - Isna Dina Mirrati, - (2020)
This study aims to analyze the effect of Sexting on romantic attachment based on gender in early adulthood in Bandung. This research is a quantitative type with a correlational design, including 767 respondents aged 20-27 years. The data that had been collected analyzed using simple linear regression, different tests with independent sample t-test. The results of the analysis of the effect of Sexting on romantic attachment get a significance of 0.000 (p<0,05) so that the hypothesis states that there is a positive and significant influence between Sexting on romantic attachment. The results of the test for differences in Sexting behaviour in the male and female groups found a significant value of 0.000 (p<0,05), the romantic attachment variable got a significant value of 0.338 (p>0,05). Pearson correlation test conducted on Sexting on romantic attachment found that there was a correlation between the Sexting variable and romantic attachment in early adulthood (p = 0.000).